Improving The Eighth Grade Students’ Reading Comprehension Achievement by Using Semantic Mapping Technique - Maulinda Yuliani; Zakiyah Tasnim; Wiwiek Eko Bindarti (Pancaran Pendidikan, 2020)
English is a foreign language (EFL) for Indonesian students. Therefore, many students still get difficulties to comprehend an English reading text that they read. To overcome the problem, this classroom action research investigated how to improve the students' active participation and their reading comprehension achievement by using Semantic Mapping technique. The research participants were the eighth-grade students at SMPN 8 Jember. Based on the results of the observation and a reading comprehension test, it can be concluded that the implementation of Semantic Mapping technique could improve the eighth-grade students’ achievement in reading comprehension of descriptive text. The research results also showed that the students became more fun and more actively participated both individually and in a group during the teaching and learning process of reading comprehension.